Characterisation of Geotechnical Properties of Residual Tropical Soils Used for Road Infrastructure: French Guiana Experience - Nait-Rabah, Ouahcène; Germain, Flavio; Estevez, Yannick; Guiraud, James; Medjigbodo, Gildas; Dias, Daniel; Maalouf, Chadi (Applied Sciences, 2023)
This paper presents the first laboratory study of four materials (three lateritic soils and one sandy soil) mainly used in road construction in French Guiana. The analysis of macroscopic behaviour by physical tests, following French standards, made it possible to classify and group the samples with respect to the rules specified in the Guide des Terrassements Routiers (GTR). According to the GTR, these raw materials could only be used as backfill materials and under very specific hydric conditions. Chemical and mineralogical characterisation by the X-ray fluorescence analysis, scanning electron microscopy observation supplemented by the X-ray microanalysis, and the infrared analysis revealed differences in the main minerals. Indeed, the presence of mineral species such as kaolinite and gibbsite and oxides such as goethite and hematite was detected. The macroscopic and microscopic characteristics of the four soils made it possible to establish a relationship between their geotechnical and mineralogical properties. Finally, the results of this study led to the conclusion that the mineralogical composition and geotechnical properties of lateritic soils must be known simultaneously to allow correct identification for their application in road construction.
Keywords: Guyane; compressive strength; geotechnical properties; laterite; tropical soil